(untitled) (Resolusi: Jurnal Sosial Politik, 2025)
Student demonstrations are a multidimensional phenomenon that causes tension between socio-political activities and academic goals in higher education institutions. This study aims to examine lecturers’ perceptions of student demonstrations at UIN Syarif Hidayatullah Jakarta and their impact on learning practices and strategies, while also exploring students’ experiences in balancing participation in demonstrations with academic demands. The research method used a qualitative case study approach with eight purposive informants, consisting of four lecturers and four students, through semi-structured interviews, participatory observation, and documentation. The analysis was conducted using descriptive narrative, emphasizing the experiences, views, and meanings experienced by the informants, with validity reinforced through triangulation of sources, techniques, and time. The results show a divergence in lecturers’ perceptions: some emphasize the pedagogical value of demonstrations as a socio-political learning experience, while others highlight the risks to student safety and academic disruption. Demonstrations enhance students’ critical analysis, cross-actor negotiation, and adaptation skills, but they also incur academic opportunity costs and psychological pressure, especially for non-activist students. The interaction between lecturer strategies, institutional responses, and student priorities creates a polarity of priorities that affects learning effectiveness. This study confirms that student demonstrations